Intervention on pre-marriage course: case of too young to be married - Agus Sulistyono, - (Foundation for Environtmental Protection and Research, 2020)
Background: Pre-marriage course is a short course before the wedding providing knowledge, understanding, and skills needed in marriage. The new course adds pre-marriage agreement on specific family planning and consents to refer the mother if she faces obstetric emergencies. This study analyzed the impact of pre-wedding course intervention in postponing the pregnancy. Methods: This was a retrospective study using medical records through home visit to the couples. Results: There were 29 couples in a one-year program at Office of Religious Affairs, Burneh Sub-district. There were 4 women (13.8%) aged <20 years old and 25 women (86.2%) aged 20-35 years old. After one year, there was 1 pregnant woman (25%) under 20 years and 6 pregnant women (24%) in other group. One women already gave birth, four women lost to follow-up. There were no complications and maternal death reported. Conclusion: This pre-marriage course had better results on reducing maternal death and postponing the pregnancy, especially for the adolescent couples.